Assessment of pathological response to neoadjuvant chemotherapy in patients with breast carcinoma using Sataloff system - Agarwal, Savita; Pandey, Pinki; Ralli, Megha; Chaturvedi, Vineet; Mittal, Kailash; Singh, Shailendra Pal (Archive of Oncology, 2019)
Background: Neoadjuvant chemotherapy is frequently administered to patients with breast carcinoma. Response to chemotherapeutic regime can be assessed clinically as well as by pathological examination of the breast tissue. It is essential to accurately categorize the patients with residual disease according to the standard guidelines for pathological evaluation of breast specimens after neoadjuvant chemotherapy. The present study was undertaken to assess the histomorphological changes in mastectomy specimens and axillary lymphatic nodes of patients receiving neoadjuvant chemotherapy, grade the pathological response using Sataloff system and to compare the clinical and pathological response after neoadjuvant chemotherapy. Methods: Present prospective study included a total of 31 patients with locally advanced breast carcinoma, diagnosed with infiltrating ductal carcinoma, not otherwise specified on biopsy specimen and subsequently treated with 2 to 6 cycles of neoadjuvant chemotherapy. Pathological response to neoadjuvant chemotherapy was assessed in breast and axillary lymphatic nodes according to Sataloff criteria. Results: Clinical response observed was complete (cCR) in four cases (12.9%), partial response (cPR) in 24 cases (77.4%), and no response (cNR) in three cases (9.7%). Based on tumor response, breast and lymph nodes were graded as pathological complete response (pCR), pathological partial response (pPR), and pathological no response (pNR) in five (16.1%), 18 (58.1%) and eight (25.8%) cases respectively using Sataloff criteria. Ductal carcinoma in situ and lymphovascular invasion were seen in 11 (35.4%) and 16 cases (51.6%), respectively. Conclusion: The pathological assessment of tumor response remains the gold standard, as neither the clinical nor the radiological responses are sensitive predictors of tumor response after treatment. However pathological examination is quite challenging and demands sufficient experience along with detailed clinical and radiological data of pre- and postoperative neoadjuvant chemotherapy for precise response evaluation.
Keywords: Pathology; Lymph; Carcinoma; Breast